A House for Three Generations and a Private Museum: Kansas City, Missouri - Therese G. Cermak (Oz, 1981)
The difficulty in writing about my Design Six thesis is trying to remember what in the hell was going on. Of course, I remember the pressure to meet deadlines and fulfill requirements…